An optimized guanidination method for large‐scale proteomic studies. Issue 13 (8th June 2016) - Ye, Juanying; Zhang, Yang; Huang, Lin; Li, Qingqing; Huang, Jingnan; Lu, Jianan; Li, Yanhong; Zhang, Xumin
Abstract : As an ε–amine specific derivatization method, guanidination is widely used in proteomic studies for mainly two reasons: the significant improvement in ionization efficiency and the selective protection of ε–amine. Herein, we employed a systematic comparison of two widely used guanidination approaches and revealed the advantages and disadvantages of each method. The sodium buffer based approach resulted in an unexpected side modification, +57 Da, which is reported for the first time; whereas the ammonium buffer based approach resulted in relatively lower yield. We carried out an optimization study by testing different buffer compositions, pH, temperatures and reaction times, and consequently discovered the optimized guanidination condition. Furthermore, we decoded the +57 Da side product as the addition of C2 H3 NO and proposed a possible mechanism of the side reaction. Importantly, our study demonstrated that mass spectrometry is a powerful tool in discovering minor side reactions which are often impossible by other techniques, and hence suggested that chemical derivatization methods should be investigated more carefully prior to extensive applications in proteomics field.